Measuring farmers' time preference: A comparison of methods - Daniel Hermann; Oliver Mußhoff; Dörte Rüther (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2015)
The discount rate is of great importance for all decisions in an intertemporal context, such as the decision of how much a society invests in environmental preservation, or the financial decisionmaking on the individual level. This study experimentally investigates the time preferences of farmers by comparing two different methods: One method is based on the measurement of time preference and risk attitude that are elicited in two parts of an experiment. Afterwards, the discount rate is adjusted using the risk attitude. The other method uses a one-parameter approach without the necessity of separately eliciting the individual risk attitude and without an assumption regarding the form of the utility function. The results reveal that, contrary to previous research, the ascertained discount rates of both methods are different. Furthermore, only the method based on the measurement of time preference and risk attitude separately reveals sensitivities regarding the prospective payout.
Keywords: 330; discount rate; experimental economics; intertemporal decision making; magnitude effect; risk attitude